Specificity and implicatures - Geist, Ljudmila; Gáspár, Edgar Onea (Proceedings of the Amsterdam Colloquium, 2007)
In this paper we argue for a unified treatment of the effects of specificity in the Russian pronominal system and in the case of differential object marking in Romanian. Based on a model of semantic underspecification and pragmatic reasoning, we claim that different readings of indefinites can be traced back to the different binding properties of an implicit argument (the referential anchor) which we postulate for specificity markers, and additional pragmatic restrictions on binding arising from conventional implicatures.